(untitled) (Praxis Educativa, 2020)
The learning experience carried out in a blended environment with 51 psychology students is reported in the fourth semester Sociocultural Theory course at a Mexican public university. A research based on design was conducted, focused on the development of skills to learn to learn and the techno-pedagogical design of personal learning environments mediated by digital technologies. The construction of electronic portfolios of the students that functioned as an integrating strategy for the entire intervention design and as evidence of the lessons learned are highlighted. The results are discussed in terms of the techno-pedagogical mediation offered and the pedagogical devices used. It is concluded that the experience conducted allowed students to advance in a better understanding of the psychologist’s professional identity and in the appropriation of digital technologies for professional practice.